Analysis of Socio-Cultural in Prime Minister Benjamin Netanyahu's Speech to Congress in Washington, DC, 2024 - Syawandi, Andy; Tawakkal, Alamsyah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The joint meeting of Congress in Washington, DC, is a congress used by Benjamin Netanyahu to seek US support, defend himself, and also convey his ideology regarding Israel's aggression against Palestine. the main focus of this research is to see how a speech can impact the socio-culture that exists in society in the economic, political, and cultural aspects. This research is taken from Benjamin Netanyahu's speech at the Joint Congress meeting in Washington, DC, 2024, which is taken from words and phrases, and by using the theory of one of the dimensions of critical discourse analysis from Norman Fairclough, namely, socio-cultural. The method of the research is qualitative as an instrument. The result of this research shows that language functions not only as a medium of communication but also as a tool of power to shape perceptions, justify actions, and influence public opinion. In his speech, Benjamin Netanyahu constructed a narrative framing Israel’s action against Palestine as a truth based on religious texts, while presenting peace as a rhetorical strategy to gain U.S. support and legitimize his political agenda. This research provides an understanding of language in the socio-cultural dimension and shows how Netanyahu uses political discourse as an instrument of power to justify Israeli aggression against Palestine and respond to international criticism.